(untitled) (World Economics and Finance Bulletin, 2022)
This article shows the role of creative marketing in organizing an innovative economy in the country. This article also describes the essence of the concept of creativity, creative marketing, the necessary conditions for the introduction of innovative marketing, types of marketing creativity